2018
DOI: 10.1038/s41598-018-35225-6
|View full text |Cite
|
Sign up to set email alerts
|

Si and Ge based metallic core/shell nanowires for nano-electronic device applications

Abstract: One dimensional heterostructure nanowires (NWs) have attracted a large attention due to the possibility of easily tuning their energy gap, a useful property for application to next generation electronic devices. In this work, we propose new core/shell NW systems where Ge and Si shells are built around very thin As and Sb cores. The modification in the electronic properties arises due to the induced compressive strain experienced by the metal core region which is attributed to the lattice-mismatch with the shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Lattice-strain-induced electronic modifications have also been observed for semiconductorcontaining core-shell materials, whereby changes can be induced in the band gap and conducting properties (which are relevant to photocatalytic activity) of the material, thus providing a high degree of tunability in the photocatalytic and electrocatalytic properties of such materials by adjusting the shell thickness. 110,111 It is important to draw attention to the similarities and differences between metal@metal core-shell structures and metal alloys. In an alloy, the atoms of one metal are incorporated in the lattice structure of another, forming a kind of (sometimes) nearly uniform solid solution.…”
Section: Benefits Of Core-shell Materials In Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lattice-strain-induced electronic modifications have also been observed for semiconductorcontaining core-shell materials, whereby changes can be induced in the band gap and conducting properties (which are relevant to photocatalytic activity) of the material, thus providing a high degree of tunability in the photocatalytic and electrocatalytic properties of such materials by adjusting the shell thickness. 110,111 It is important to draw attention to the similarities and differences between metal@metal core-shell structures and metal alloys. In an alloy, the atoms of one metal are incorporated in the lattice structure of another, forming a kind of (sometimes) nearly uniform solid solution.…”
Section: Benefits Of Core-shell Materials In Catalysismentioning
confidence: 99%
“…Huang et al 221 proposed that introducing Au atoms with their greater atomic radius as the core material in Au@Cu coreshell structures would increase the tensile strain on the surface Cu atoms and lower the overpotential for CO 2 -RR to methane to À0.64 V (vs. RHE). Liu et al 40 conducted a DFT calculation for a core-shell type Cu-M (M = Ni, Co, Rh, Ir, Pt, Pd) heterostructure and concluded that the overpotential required for CO 2 reduction can be lowered by 0.17 V on Cu (3 monolayers)-Ir catalyst relative to the value for Cu (111). The authors proposed that apart from the lattice strain effect of the core-shell structure, the ligand effect of the Ir substrate also had a significant effect on the adsorption energies of the key intermediates.…”
Section: Electrocatalytic Co 2 Reduction To Hydrocarbons/oxygenatesmentioning
confidence: 99%
“…The electronic properties of the Sb/Ge NWs are different from those of the pure Sb and Ge-NWs. The change in the electronic properties is due to the induced compressive strain experienced by the metal core region due to its lattice-mismatch with the shell region as we have explained in our previous work 40 . The band lines crossing the Fermi energy give rise to a quantum conductance measured in units of G 0 = 2e 2 /h, where e is the unit of charge and h is the Planck’s constant 41 .…”
Section: Resultsmentioning
confidence: 66%
“…The current is calculated to 140 μA and 127 μA for Pd/Si (1R) and Pt/Si (1R), respectively at 1.0 V, while the Pd/Ge and Pt/Ge shows the current value of 75.3 μA and 68.5 μA, respectively. It is also observed that these NWs show a high magnitude of current at corresponding applied voltage comparing to Sb 29 , As 29 and Ni 30 core, wrapped with same shell material and same diameter.…”
Section: Resultsmentioning
confidence: 76%